Aetiology, diagnosis and management of halitosis - a narrative review - Justyna Grudziąż-Sękowska; Ewa Iwanicka-Grzegorek (Kazimierz Wielki University, 2022)
Objectives The present study aimed to present an overview of the aetiology of oral malodour and the diagnostic and treatment procedures. Design A comprehensive review of scientific literature (up to December 2021) was conducted using Medline and PubMed databases and Google Scholar, including checking reference lists of journal articles by hand-searching. Results are presented descriptively for halitosis's aetiology, diagnosis and clinical management. Results The origin of the foul odour problem is mainly due to intra-oral causes, while only a proportion of cases result from additional systemic problems. In some cases, the problem can be caused by co-existing oral and extraoral problems. Evidence suggests that the leading cause of intra-oral halitosis is the anaerobic microorganisms present in the tongue plaque. Less commonly, the foul odour is due to poor oral hygiene and periodontitis. Conclusion The origin of the foul odour problem is mainly due to intra-oral causes, while only a proportion of cases result from additional systemic problems. Dentists need to analyse and treat the oral problems that may be responsible for the patient's malodour, as well as inform the patient about the causes of the foul odour and oral hygiene procedures (flossing, tongue cleaning, selection and use of appropriate mouthwash and toothpaste). If the problem persists, they should know whom to refer the patient to for further diagnosis. It is reasonable to organise consultations on halitosis in a multidisciplinary setting - periodontists, otolaryngologists (ENT specialists), internal medicine specialists, gastroenterologists, psychiatrists, psychologists and others.